Strategi Kreatif Pembelajaran Bahasa Arab Untuk Anak Usia Dini Di Tk Zainul Hasan Genggong: Meningkatkan Kemampuan Berbahasa Dengan Media Inovatif - Muzammil, Ahmad (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
This study aims to identify the factors influencing the implementation of Arabic language learning strategies for early childhood in class "B" at TK Zainul Hasan Genggong Probolinggo. Arabic language learning at this kindergarten is expected to provide an enjoyable and effective experience for children, developing their language skills through various appropriate methods and media. The factors influencing the implementation of learning include the quality and creativity of the teacher, the children’s abilities and interests, the availability of engaging learning media, and support from the school and family environment. The use of media such as songs, images, and games, as well as the application of methods suitable for child development, are key to successful learning. Furthermore, parental involvement and the social environment also strengthen the learning process. Overall, internal and external factors that support each other can create an effective and enjoyable learning environment for early childhood in learning Arabic.